Використання композиційного рідкого палива в енергетиці України - Макаров, А.С.; Косигіна, І.М.; Кручко, І.М. (Вісник НАН України, 2022)
У статті запропоновано застосування на підприємствах енергетичного
комплексу замість вугілля композиційного рідкого палива з метою зменшення шкідливого впливу на довкілля і підвищення коефіцієнта корисної дії теплових електростанцій. Обґрунтовано доцільність використання в
промислових енергоустановках композиційного рідкого палива, показано
його переваги порівняно з традиційними видами енергетичного палива. Запропоновано технологічну схему приготування композиційного палива на основі вугілля і рідких органічних відходів з добавками пластифікаторів та
стабілізаторів, яка дозволяє не лише утилізувати промислові відходи, що
містять органічні речовини, а й знизити рівень викидів шкідливих речовин. Energy complex enterprises operating on traditional hydrocarbon energy resources, including solid fuel (coal), annually
produce tens of millions of tons of ash and slag waste (ASW) and hundreds of millions of cubic meters of gaseous emissions.
To reduce the harmful impact on the environment and increase the efficiency of thermal power plants, it is proposed
to use liquid composite fuel instead of pulverized and layered coal combustion. The expediency of using composite
liquid fuel (CLF) in industrial power plants is substantiated. The advantages of using CLF as an energy fuel in comparison
with traditional fuels are shown. A technological scheme for the preparation of composite fuel based on coal and
liquid organic waste, with the addition of plasticizers and stabilizers, is proposed. This technology allows not only to
dispose of production waste containing organic substances, but also to reduce the amount of harmful substances formed
during the combustion of various types of fuel.